Sampling variability of percutaneous liver biopsy in primary sclerosing cholangitis. Issue 10 (October 1995) - Olsson, R; Hägerstrand, I; Broomé, U; Danielsson, A; Järnerot, G; Lööf, L; Prytz, H; Rydén, B O; Wallerstedt, S
Abstract : AIMS--To study sampling variability of percutaneous liver biopsy in primary sclerosing cholangitis (PSC). METHODS--One hundred and twelve biopsy specimens (that is, 56 pairs) from 44 patients with PSC, confirmed by cholangiography, were evaluated blindly. Six different features, qualitative grading of four other features and staging according to Ludwig were assessed. RESULTS--Quantitative sampling variability was confined mainly to just one grade or stage, although 11% (six of 56) of the biopsy specimen pairs differed by more than one stage (7% (one of 15) in pairs > 2 cm in length). Qualitative sampling variabilities were between 18 and 71%. Advanced disease (stages 3 or 4) was missed in 40% (two of five) of the biopsy specimens while cirrhosis was missed in 37%. CONCLUSION--Paired liver biopsy specimens should be taken in clinical studies of PSC using liver histology for evaluation or prognosis.